Public Opinion in Karanganyar Regency on The Preventive Function of The Public Prosecutor's Office in Efforts to Control and Enforce Criminal Acts - Berliana Kinanthi Mukti; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
This research was prepared with the aim of obtaining information about the opinion of the community, especially the Karanganyar District community, Karanganyar Regency, regarding the application of the function of law enforcement officials in this case the public prosecutor's office, namely the preventive function as an effort to prevent criminal acts in the community. The research uses a sociological approach in the context of empirical law involving empirical data analysis to understand legal phenomena in society. In addition, the statutory approach is used to analyze the relevant legal framework. The data collection techniques used are interview techniques with randomly selected respondents from the Karanganyar District community of Karanganyar Regency and literature study techniques from primary data in the form of laws and regulations and legal events. Unlike the journal of Education and Development Institut Pendidikan Tapanuli Selatan, entitled